The crystal and molecular structure of 2'-deoxy-2'-fluoroinosine monohydrate. - Hakoshima, T (1981)
The structure of the hydrate of 2'-deoxy-2'-fluoroinosine has been determined by single-crystal x-ray diffraction. The nucleoside crystallizes in space group P2(1)2(1)2(1) with unit cell dimensions, a = 33.291, b = 10. 871, c = 6.897A. There are two nucleosides and two water molecules in the asymmetric unit. The structure was solved by direct methods and refined to a residual R = 0.095. The two independent nucleosides in the asymmetric unit show different conformations about the glycosidic bond, while other structural details are similar. The base orientation to the sugar is syn in molecule A, whereas anti in molecule B. The exocyclic C(4')-C(5') bond conformation defined with respect to C(3')-C(4')-C(5')-O(5') is gauche+ in both molecules A and B. The sugar ring pucker defined by the pseudorotation phase angle P is a twisted conformation in both, C(3')-endo-C(4')-exo with P = 29 degrees in molecule A and C(4')-exo-C(3')-endo with P = 41 degrees in molecule B. It is shown by comparison with x-ray results of other 2'-fluoronucleosides and unmodified nucleosides including inosines that, in addition to a strong preference of the C(3')-endo type pucker, twisted conformations involving C(4')-exo puckering may be one of characteristic features of 2'-fluoronucleosides.